6x-y-5=0

Simple and best practice solution for 6x-y-5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-y-5=0 equation:


Simplifying
6x + -1y + -5 = 0

Reorder the terms:
-5 + 6x + -1y = 0

Solving
-5 + 6x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 6x + 5 + -1y = 0 + 5

Reorder the terms:
-5 + 5 + 6x + -1y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 6x + -1y = 0 + 5
6x + -1y = 0 + 5

Combine like terms: 0 + 5 = 5
6x + -1y = 5

Add 'y' to each side of the equation.
6x + -1y + y = 5 + y

Combine like terms: -1y + y = 0
6x + 0 = 5 + y
6x = 5 + y

Divide each side by '6'.
x = 0.8333333333 + 0.1666666667y

Simplifying
x = 0.8333333333 + 0.1666666667y

See similar equations:

| 6(x+5)=6(x+11) | | 45=-5x | | 4(4x+3)=15x+10 | | 4x+2+3x=5x+14+x | | a^3+b^3+c^3=21 | | 9t=-10t-3 | | -5(2x-9)=2(x-8)11 | | 20x^3+8x^2+12x= | | 4-18=z/-9 | | 12x-8=11x | | 2x^2+8x+6=8 | | 9w-8w+2=-4+2w | | 3/4c=72 | | 5j-440=30 | | 3D-10=6-5d | | -3(x-4)=-1 | | 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 | | 6-3z=-5z-8 | | g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 | | 6x+13=-5x-18 | | -9+9p=10p | | -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 |

Equations solver categories